2022
DOI: 10.1021/acs.energyfuels.2c03055
|View full text |Cite
|
Sign up to set email alerts
|

Review and Perspectives on CO2 Bubble Dynamic Characteristics in Different Liquids during Carbon Capture, Utilization, and Storage Process

Abstract: Carbon dioxide (CO 2 ) bubbles are common during carbon capture, utilization, and storage (CCUS) processes and have many impacts on water conservancy machinery, metallurgy, and the chemical industry. To explore the dynamic characteristics of CO 2 bubbles in different liquids in CCUS, the motion mechanism of CO 2 bubbles was integrated, and the effects of different liquid characteristics and different external conditions on the dynamic characteristics of CO 2 bubbles were classified and summarized. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…In the context of carbon control strategies, scholars globally have explored various technologies and methods for reducing carbon emissions from multifaceted perspectives and dimensions. These approaches encompass energy restructuring, innovation in green energy technology, optimization of industrial structures, mechanisms of carbon trading markets, carbon taxation, judicious application of carbon pricing mechanisms, and the deployment of carbon dioxide capture and storage technologies. Grossman et al categorized the diverse strategies for carbon emission reduction and concluded that at a macro level, CO 2 emission reductions are primarily achieved through three mechanisms: scale effect, technological effect, and structural effect. It is evident that the economic scale, industrial structure, and technological advancement are pivotal factors influencing carbon emissions.…”
Section: Carbon Reduction Technologies and Methods In The Context Of ...mentioning
confidence: 99%
“…In the context of carbon control strategies, scholars globally have explored various technologies and methods for reducing carbon emissions from multifaceted perspectives and dimensions. These approaches encompass energy restructuring, innovation in green energy technology, optimization of industrial structures, mechanisms of carbon trading markets, carbon taxation, judicious application of carbon pricing mechanisms, and the deployment of carbon dioxide capture and storage technologies. Grossman et al categorized the diverse strategies for carbon emission reduction and concluded that at a macro level, CO 2 emission reductions are primarily achieved through three mechanisms: scale effect, technological effect, and structural effect. It is evident that the economic scale, industrial structure, and technological advancement are pivotal factors influencing carbon emissions.…”
Section: Carbon Reduction Technologies and Methods In The Context Of ...mentioning
confidence: 99%
“…Its paramount importance relies not only on its wide application in many different industrial operations but also on its broad occurrence in numerous natural processes, such as methane seep in marine fissures or gas bubbles in volcano eruptions 1,2 . Regarding technical applications, bubble rising is relevant in areas as diverse as water treatment, mineral flotation, carbon capture, drag reduction, ocean microplastics scavenging, or medical treatment and diagnosis, among many other techniques [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…2 Carbon capture, utilization, and storage (CCUS) can be used to meet these goals. 3 The absorption method is the most commonly used carbon capture method in industry and practical application, and the absorbent has a crucial effect on the absorption process; thus, the choice of the absorbent is directly relevant to the decarbonization effect. 4 In 1995, Choi was the first to refer to a stable suspension formed by the uniform dispersion of tiny particles in a liquid as nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…To fulfill the Paris Agreement’s 1.5 °C targets, global CO 2 emissions were set to fall 45% below 2010 levels by 2030 and then become carbon-neutral by 2050 . Carbon capture, utilization, and storage (CCUS) can be used to meet these goals . The absorption method is the most commonly used carbon capture method in industry and practical application, and the absorbent has a crucial effect on the absorption process; thus, the choice of the absorbent is directly relevant to the decarbonization effect …”
Section: Introductionmentioning
confidence: 99%